A new experiments-based methodology to define the stability threshold for any vehicle exposed to flooding. Issue 9 (21st October 2017) - Martínez-Gomariz, Eduardo; Gómez, Manuel; Russo, Beniamino; Djordjević, Slobodan
Abstract: A vehicle exposed to flooding, after losing stability, becomes buoyant and may be washed away with potential injuries and fatalities. Such vehicles cause additional disruption to traffic that is already affected by flooding, which may lead to substantial indirect economic impact, especially in urban areas. Therefore, the analysis of the stability of vehicles exposed to flooding is important in order to make decisions to reduce damages and hazards. In this research, based on an experimental campaign that included a range of twelve car models, a new methodology to obtain the stability threshold for any real vehicle exposed to flooding is developed. A stability coefficient (SCmod ) is derived with which the vehicles can be sorted by stability against water flows and their stability functions may be determined. The experiments were conducted with three different model scales (1:14, 1:18 and 1:24) and involved analysis of both friction and buoyancy effects, which made this the most comprehensive research study to date. This methodology enables the definition of a stable area in the flow depth-velocity domain for any real vehicle. A tool is provided that decision-makers in the field of urban flood risk management can employ and after defining a design vehicle they can obtain its corresponding stability threshold.